Respuesta :

Answer:

a) 0.071

b) 0.884

Step-by-step explanation:

a)

7.1 * 10^(2) = 7.1 * 0.01 = 0.071

b)

(6.8 * 10^2) * (1.3 * 10^(-3)) = 6.8 * 1.3 * 10^2 * 10^(-3) = 8.84 * 10^(-1) = 8.84 * 0.1 = 0.884

Answer:

a) 0.071

b) 0.884

Step-by-step explanation:

b) explanation

Group coefficients together and exponents together to multiply numbers in scientific notation.

(6.8 ⋅ 1.3) (10^2 ⋅ 10^−3)

Multiply 6.8 by 1.3

8.84 (10^2 ⋅ 10^−3)

Use the power rule a^m a^n = a^m+n  to combine exponents.

8.84 ⋅ 10^2 − 3

Subtract 3 from 2

8.84 ⋅ 10^ − 1

Convert  8.84 ⋅ 10^ − 1

from scientific notation.

0.884

hope this helps :) sorry I didn't include an explanation for a

p.s. i really need brainliest :)